The patient with chronic cough: a challenge for the physician. (Colombia Medica, 2006)
For the family physician the handling of chronic illnesses or not well defined pathological processes, mean a daily challenge. The clinical case of a 47 year-old patient is presented with permanent cough two years old. Their life committed for labor desertion and dysfunction psicosocial, nevertheless its valuation for diverse specialists with multiple helps diagnoses and varied treatments. The family physicians based on their training and experience, with a systemic focus, designed a plan of good work to discern the cause of the patient’s chronic cough and to provide the handling for the permanent control of the symptom.